Unlocking Wellness: Probiotics as Key Drivers in Functional Food Innovation and Health Promotion - Yifei Huang; Yuankun Zhou; Hengyi Xu (Applied Sciences, 2025)
Probiotics play a pivotal role in functional food development owing to their distinct health-promoting properties. This review comprehensively examines probiotics’ classifications and functional mechanisms and their roles in modulating intestinal microbiota, enhancing immunity, and intervening in metabolic diseases. The diverse applications of probiotics in dairy and meat products are examined alongside technological innovations, including microencapsulation, biofilm systems, and personalized strain screening that have been employed to enhance probiotic stability and efficacy in functional foods. We analyze safety concerns and regulatory challenges, emphasizing the need for rigorous pre-market evaluation and international regulatory harmonization. This study aims to review the existing scientific evidence on the application of probiotics in functional foods, providing a theoretical reference for the development of the next generation of high-quality functional foods.